1976
DOI: 10.1007/bf00418905
|View full text |Cite
|
Sign up to set email alerts
|

Biologische Effekte von Bariumsulfat als R�ntgenkontrastmittelbeimengung in Knochenzementen

Abstract: The investigations presented in this paper concern the question of toxicity of Bariumsulfate as an ingredient of bone-cement. In 6 rabbits the medullary cavity of the right femur was filled with bone-cement which contained Bariumsulfate as X-ray contrast ingredient and the left one with BaSO4-free bone-cement. 4 1/2 months post operationem the femura were investigated by histological and microradiographic methods. The status of both sides was compared. On the BaSO4-containing side regularly necrotic lamellar b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…To realize the multifunction, further surface modification of this porous BaSO 4 microparticle is carried out. In this study, PDA coating is used as a platform for modification, which is an easy method for surface modification, is not only applied to modify most materials but also forms functional groups for further reaction [17,20,21,22]. EDS result shows that Ag and I-CD are modified on the surface of porous BaSO 4 microparticles with the help of PDA coating.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To realize the multifunction, further surface modification of this porous BaSO 4 microparticle is carried out. In this study, PDA coating is used as a platform for modification, which is an easy method for surface modification, is not only applied to modify most materials but also forms functional groups for further reaction [17,20,21,22]. EDS result shows that Ag and I-CD are modified on the surface of porous BaSO 4 microparticles with the help of PDA coating.…”
Section: Discussionmentioning
confidence: 99%
“…Silver-based nanomaterials are known for their strong antibacterial activities for a lot of bacteria [17,21,22]. Previous studies indicated the presence of catechol structure in polydopamine could inhibit the growth and proliferation of bacteria in some extent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations